(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article reviews Chinese-Uzbek relations, focusing on distinct spheres of cooperation, namely economic, cultural, security along with the participation in international organizations. By using the constructivist framework, the study highlights the way shared identities and social constructs have shaped bilateral relations. Through the analysis of statistics, official agreements and historical exchanges this article sets a goal to showcase profound ways in which constructivism has influenced the dynamics of Chinese-Uzbek relations. The research explores the evolving nature of cooperation in the areas provided and emphasizes the strategic significance of partnership in light of regional stability and mutual prosperity.